Gender, Human Capital and Growth Evidence from Six Latin American Countries - Robbins, Donald J.. (OECD Development Centre Working Papers, 1999)
This Technical Paper reports on a body of research conducted for the OECD Development Centre by Donald J. Robbins. It examines the patterns and determinants of rapidly rising educational attainment in six Latin American countries - Argentina, Chile, Colombia, Costa Rica, Mexico and Uruguay - all of which illustrate the sweeping transformations in growth, demographics and education now occurring in much of the world. It finds that rising per capita output, through a mechanism which induces women to join the labour force and interacts with falling family size, acts as the key factor leading to mounting educational achievement. This in fact highlights the role of women in basic household microeconomic decisions with powerful economic and social effects - decisions about female labour-force participation and family shifts from notions of "quantity" (large families) to those of "quality" (fewer children, with more investment in health and education). It carries important implications ...